Determinação da influência de componentes de placas de circuito impresso de tablets no crescimento de Acidithiobacillus Ferrooxidans-LR - Moreira, Izabella Vicentin (2019)
Tablets share maket with smartphones and notebooks, electrical and electronic equipments (EEE), reaching the worldwide sales mark of 248 million units in 2015. These EEE are part of the group of new waste electrical and electronic equipment (WEEE). The bioleaching is a recycling process used to leach metals through microorganisms’ metabolism, and has been studied to recover metals from WEEE, mainly printed circuit boards (PCB). Its advantages are related to cost and toxic gases emission, comparing to hydrometallurgy and pyrometallurgy. However the disadvantage is the process time, way higher than the others, which is a decisive aspect to the industry. Authors suggest time could be influenced by the toxicity of some PCB components to the bacterium. Thus, the main purpose of this research was to determine if PCB components influence Acidithiobacillus ferrooxidans-LR growth, applied in bioleaching process. The methodology occurred in three stages. In the First Stage the characterization of the tablets’ PCB was carried through the digestion in aqua regia, resulting in 33% of ceramic, 32% of polymeric and 35% of metallic (Cu, Ni, Sn, Pb, Zn, Ag, Au, Pt, Mn, Sr, among others) portion. During the Second Stage the parameters of copper bioleaching were tested, monitoring the pH, ferrous ions and copper concentration. The pulp densities of 15g.L-1 was chosen to carry out the Third Stage. At the last stage the influence of glass fiber, glass fiber with epoxy resin, metals and capacitors were determined. The epoxy resin presented microbiostatic, and the metals microbiocide effect to the bacterium grouth, the other components did not presented any effect. Lastly, the metals were tested separated. Ag and Sn presented microbiocide effect to the bacterium, and Cu microbiostatic. Therefore, it is possible to conclude that studies on alternatives to the use of epoxy resin, silver, tin and copper in WEEE, or on process to avoid contact of these componets and the bacterium are essential to the bioleaching process improvement.